’Tough ain’t enough’: Representation of Personal Identity in Clint Eastwood Films - Morais, Ana Bela (2016)
By reflecting on films such as Unforgiven (1992), A Perfect World (1993), Gran Torino (2008), and especially Million Dollar Baby (2004), we intend to examine in a critical manner the way the hero and his personal identity are portrayed and thought of in Clint Eastwood films. The aim of this study is to try to understand the existential problems faced by the main characters, concerning their relationships with themselves and with their close family- whether blood relatives or symbolic family.